Outcomes of Patients Undergoing Elective Bowel Resection Before and After Implementation of an Anemia Screening and Treatment Program. Issue 11 (19th August 2022) - Gilbert, Richard W.D.; Zwiep, Terry; Greenberg, Joshua; Lenet, Tori; Touchie, Donna L.; Perelman, Iris; Musselman, Reilly; Williams, Lara; Raiche, Isabelle; McIsaac, Daniel I.; Thavorn, Kednapa; Fergusson, Dean; et al.
Abstract : BACKGROUND : Patients with anemia undergoing elective colorectal cancer surgery are known to have significantly higher rates of postoperative complications and worse outcomes. OBJECTIVE: This study aimed to improve rates of anemia screening and treatment in patients undergoing elective colon and rectal resections through a quality improvement initiative. DESIGN: We compared a historical cohort of patients before implementation of our anemia screening and treatment quality improvement program to a prospective cohort after implementation. SETTINGS: This study was conducted at a tertiary care hospital. PATIENTS: This study included all adult patients with a new diagnosis of colon or rectal cancer without evidence of metastatic disease between 2017 and 2019. INTERVENTIONS: The interventions include the anemia screening and treatment quality improvement program. MAIN OUTCOME MEASURES: The primary outcome was hospital cost per admission. RESULTS: This study includes a total of 84 patients who underwent elective colon or rectal resection before implementation of our anemia quality improvement project and 88 patients who underwent surgery after. In the preimplementation cohort 44 of 84 patients (55.9%) were anemic compared to 47 of 99 patients (54.7%) in the postimplementation cohort. Rates of screening (25%–86.4%) and treatment (27.8%– 63.8%) were significantly increased in the postimplementation cohort. Mean total cost per admission was significantly decreased in the postimplementation cohort (mean cost $16, 827 vs $25, 796; p = 0.004); this significant reduction was observed even after adjusting for relevant confounding factors (ratio of means: 0.74; 95% CI, 0.65–0.85). The mechanistic link between treatment of anemia and reductions in cost remains unknown. No significant difference was found in rates of blood transfusion, complications, or mortality between the groups. LIMITATIONS: The study limitation includes before-after design subjected to selection and temporal biases. CONCLUSIONS: We demonstrate the successful implementation of an anemia screening and treatment program. This program was associated with significantly reduced cost per admission. This work demonstrates possible value and benefits of implementation of an anemia screening and treatment program. See Video Abstract at http://links.lww.com/DCR/C15 . RESULTADOS DE LOS PACIENTES SOMETIDOS A RESECCIÓN INTESTINAL ELECTIVA ANTES Y DESPUÉS DE LA IMPLEMENTACIÓN DE UN PROGRAMA DE DETECCIÓN Y TRATAMIENTO DE ANEMIA ANTECEDENTES: Se sabe que los pacientes anémicos que se someten a una cirugía electiva de cáncer colorrectal tienen tasas significativamente más altas de complicaciones posoperatorias y peores resultados. OBJETIVO: Mejorar las tasas de detección y tratamiento de la anemia en pacientes sometidos a resecciones electivas de colon y recto a través de una iniciativa de mejora de calidad. DISEÑO: Comparamos una cohorte histórica de pacientes antes de la implementación de nuestro programa de detección de anemia y mejora de la calidad del tratamiento con una cohorte prospectiva después de la implementación. ENTORNO CLINICO: Hospital de atención terciaria. PACIENTES: Todos los pacientes adultos con un nuevo diagnóstico de cáncer de colon o recto sin evidencia de enfermedad metastásica entre 2017 y 2019. INTERVENCIONES: Detección de anemia y programa de mejora de la calidad del tratamiento. PRINCIPALES MEDIDAS DE RESULTADO: El resultado primario fue el costo hospitalario por ingreso. RESULTADOS: Un total de 84 pacientes se sometieron a resección electiva de colon o recto antes de la implementación de nuestro proyecto de mejora de calidad de la anemia y 88 pacientes se sometieron a cirugía después. En la cohorte previa a la implementación, 44/84 (55, 9 %) presentaban anemia en comparación con 47/99 (54, 7 %) en la cohorte posterior a la implementación. Las tasas de detección (25 % a 86, 4 %) y tratamiento (27, 8 % a 63, 8 %) aumentaron significativamente en la cohorte posterior a la implementación. El costo total medio por admisión se redujo significativamente en la cohorte posterior a la implementación (costo medio $16 827 vs. $25 796, p = 0, 004); esta reducción significativa se observó incluso después de ajustar los factores de confusión relevantes (proporción de medias: 0, 74, IC del 95 %: 0, 65 a 0, 85). El vínculo mecánico entre el tratamiento de la anemia y la reducción de costos sigue siendo desconocido. No hubo diferencias significativas en las tasas de transfusión de sangre, complicaciones o mortalidad entre los grupos. LIMITACIONES: El diseño de antes y después está sujeto a sesgos temporales y de selección. CONCLUSIONES: Demostramos la implementación exitosa de un programa de detección y tratamiento de anemia. Este programa se asoció con un costo por admisión significativamente reducido. Este trabajo demuestra el valor y los beneficios posibles de la implementación de un programa de detección y tratamiento de la anemia. Consulte Video Resumen en http://links.lww.com/DCR/C15 . (Traducción— Dr. Francisco M. Abarca-Rendon )